Hubungan Antara Bimbingan Orang Tua Dan Bimbingan Guru Dalam Belajar Dengan Hasil Belajar Siswa Kelas IV SDN 15 Ampenan - Vivilia Ananda; I Nyoman Karma; Heri Hadi Saputra (Pendagogia: Jurnal Pendidikan Dasar, 2021)
This study aims to determine the relationship between parental guidance and teacher guidance in learning with the learning outcomes of fourth-grade students at SDN 15 Ampenan. The problem in this study is that the learning outcomes of fourth-grade students at SDN 15 Ampenan are still below the minimum criteria of mastery learning (KKM). This research is quantitative research with a correlational analysis technique. The subjects of this study were 44 fourth-grade students at SDN 15 Ampenan. Data collection techniques in this study using questionnaires and documentation.The hyphothesis test used product-moment correlation and multiple correlations. Based on the results of the study, it showed that (1) there is no relationship between parental guidance and the fourth-grade student learning outcomes of SDN 15 Ampenan. It is evidenced from the results of the product-moment correlation analysis that the value of r count = 0.180 is lower than r table = 0.297 at a significance level of 5%. (2) there is no relationship between teacher guidance and student learning outcomes for class IV SDN 15 Ampenan. It is evidenced from the results of the product-moment correlation analysis that the value of r count = 0.148 is lower than r table = 0.297 at a significance level of 5%. (3) there is no relationship between parental guidance and teacher guidance in learning with fourth-grade student learning outcomes at SDN 15 Ampenan. It is evidence from the results of multiple correlation analysis obtained by the value of F change = 0.513 > 0.05, it can be concluded that the variables of parental guidance and teacher guidance simultaneously have no relationship with the learning outcomes of fourth-grade students at SDN 15 Ampenan.